PERTUMBUHAN DAN MORTALITAS IKAN ENDEMIK BUTINI (Glossogobius matanensis Weber, 1913) DI DANAU TOWUTI, SULAWESI SELATAN [Growth and Mortality of Endemic Fish Butini (Glossogobius matanensis Weber,1913) in Lake Towuti, South Sulawesi] - Mamangkey, Jefry Jack; Nasution, Syahroma Husni (BERITA BIOLOGI, 2014)
Lake Towuti is the largest lake in the Malili Complex covering the area of 560 km and 203 m in depth. Butini is an endemic and vulnerable fish species that consumed by the local people and have an important economic value. Various activities occured in the lake was thought to be the cause of decreasing fish populations.The objective of this study was to determine the growth and mortality of butini in Lake Towuti.This research was conducted in Lake Towuti for 12 months from Mei 2006 to April 2007.Fish samples obtained by using long lines with various number of hooks i.e. 8,10,12,14,and 16.Each depth (25, 50, 75, 100, 150, and 200 m) launched one long line unit in three zones (A, B, and C).Growth and fish mortality were calculated based on total length frequency data using FiSAT II software. The results showed that the longest size (46.20 cm) was the male found at a depth of -1,200(t-to)150 m in April in Zone C.The combined Von Bertalanffyâs growth pattern was of L(t)= 46,62 [1 - e ]. While the growth pattern for each male -0,950(t-to) -0,820(t-to) and female was L(t) =46,62 [1 - e ] and L(t)= 46,62 [1 - e ] respectively. The highest total mortality was found in Zone B (5.49 per year) occurred in female fish. The highest natural mortality was observed in Zone B (1.80 per year) occurred in male fish.The highest fishing mortality was recorded in zone B (4.08 per year) and found in female fish. The highest exploitation level was found in zone A (E = 0.76) recorded in female fish.Exploitation level of butini stock in Lake Towuti indicated over-fishing (E=0.56) recorded in Zone A.